Psychological analysis of the level of aggression in the male judokas socjety - Marta Wojdat; Patrycja Janowska; Małgorzata Pujszo; Robert Stępniak; Marek Adam (Kazimierz Wielki University, 2017)
The phenomenon of aggression was the subject of research both in term of its negative effects, and as a desirable element in martial arts. Determination  the level of aggression of active and former players judo, and correlation between  aggression of judokas and sociodemographic  factors was the goal of this study. The test results indicated the unusual relationship of judokas aggression  with other determinants of social life and sporting career.